Forms of capital, fictitious wealth, and the externalisation of recent capitalist crises - Nakatani, Paulo; Carcanholo, Marcelo Dias; Sabadini, Mauricio de Souza (Argumentum, 2025)
This article identifies the characteristics and particularities of recent capitalist wealth and crises based on the functional forms of capital and its processes of autonomisation and Marx’s (1985) fictitious capital in particular. In addition to explaining the constitution of the forms of capital, it discusses some indicators that point to the expressions of capitalist crises observed at the end of the 20th and beginning of the 21st centuries.
Keywords: Fictitious capital; crises; fictitious wealth; contemporary capitalism